Digital payment adoption: the antecedent of habit and behavioral intention - Ali Mohamad Rezza; Suci Fika Widyana; Angga Dewi Anggraeni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Despite the advancement in digital payment systems and banking in Indonesia, the adoption of this technology among service users is far from guaranteed. Recent data infers that the usage of digital payment systems and digital banking technology in Indonesia is still developing. A mere 55.80% of users have embraced electronic money for less than a year. This indicates ample room for growth and improvement in the country's digital finance industry. This study aims to explore and understand the factors that predict the adoption and behavioural intention of e-wallets in Indonesia. By utilizing hedonic motivation, habit, self-efficacy, and trust as critical predictors, the research model sheds light on the drivers of customer adoption of e-wallets. Data from a survey of 217 Indonesian customers were analyzed using Structural Equation Modeling (SEM) with Partial Least Square to examine the structural model. The research findings suggest that trust and habit greatly influence the intention to use e-wallets. However, an interesting discovery is that while previous literature indicated that behavioural intention was a key driver of technology usage, habit plays a more crucial role in adopting digital payment technology in this research.